Comparison of the Effectiveness of Digital and Television Advertising Elements at Gojek Indonesia Company - Jayawinangun, Roni; Nuradam, Rafli; Cahyaningrum, Qoute Nuraini (Sekolah Tinggi Ilmu Ekonomi Y.A.I - Jakarta - Indonesia, 2025)
This study aims to compare Gojek's digital advertising with television advertisements using the AIDA model. A comparative quantitative methodology was utilized in Bogor City. This study examined Gojek users who were exposed to advertisements on both digital media and television. Data were collected through questionnaires using convenience sampling and the Lemeshow formula to determine the sample size. A total of 129 respondents were analysed using the Mann-Whitney nonparametric test. The findings reveal that the average evaluation of Gojek's digital advertising elements is higher than that of television advertisements, showing a significant difference between them. This implies that advertising media choice, based on advertising elements, can have varying impacts on the effectiveness of each medium. Media selection can be tailored to specific companies, such as Gojek in Indonesia, which operates in the technology and transportation sectors and achieves a more effective impact through digital media than through television advertisements. The novelty of this study lies in the use of advertising elements as comparative indicators, in addition, research related to advertising in online transportation companies is still limited, especially in terms of media comparison. Abstrak - Penelitian ini bertujuan untuk membandingkan iklan digital Gojek dengan iklan televisi menggunakan model AIDA. Metodologi kuantitatif komparatif digunakan di Kota Bogor. Penelitian ini mengkaji pengguna Gojek yang terpapar iklan baik di media digital maupun televisi. Data dikumpulkan melalui kuesioner dengan teknik convenience sampling dan rumus Lemeshow untuk menentukan ukuran sampel. Sebanyak 129 responden dianalisis menggunakan uji nonparametrik Mann-Whitney. Temuan penelitian menunjukkan bahwa rata-rata penilaian terhadap elemen iklan digital Gojek lebih tinggi dibandingkan dengan iklan televisi, menunjukkan perbedaan signifikan di antara keduanya. Hal ini mengimplikasikan bahwa pemilihan media iklan, berdasarkan elemen-elemen iklan, dapat memberikan dampak yang berbeda terhadap efektivitas tiap media. Pemilihan media dapat disesuaikan dengan perusahaan tertentu, seperti Gojek di Indonesia, yang bergerak di sektor teknologi dan transportasi serta mencapai dampak yang lebih efektif melalui media digital dibandingkan dengan iklan televisi. Kebaruan penelitian ini terletak pada penggunaan elemen iklan sebagai indikator pembanding, selain itu penelitian terkait periklanan pada perusahaan transportasi online masih relatif terbatas terutama pada perbandingan media.